Antibacterial Activities of Kombucha Tea From Some Types of Variations of Tea on Escherichia coli and Staphylococcus aureus - Witri Nofita Safitri; Irdawati Irdawati (UNIVERSITAS NEGERI PADANG, 2020)
Tea can be used as a fermented drink called kombucha tea. Based on the oxidation process tea is classified into white tea, green tea, oolong tea and black tea. The compounds produced from the fermentation of kombucha tea have a fairly good antibacterial effect. This study aims to determine the antibacterial activity of kombucha tea fermentation from several variations of tea types against Escherichia coli and Staphylococcus aureus. This research is an experimental study with a completely randomized design (CRD) with 5 treatments and 3 replications conducted in May-June 2019 at the Microbiology Laboratory and the Integrated Research Laboratory of the Department of Biology FMIPA UNP. Kombucha tea used in this study was white tea, green tea, oolong tea and black tea. Antibacterial activity test was carried out by paper disc diffusion method against microbial test of S. aureus and E. coli bacteria. Research results showed that the highest antibacterial activity of kombucha tea fermentation in E.coli was found in black tea with a value of 1.64 cm and the lowest in tea white with a value of 1.04 cm. In S. aureus the highest value was obtained in black tea with a value of 2.48 cm and the lowest in white tea with a value of 1.39 cm.